Effect of inoculum concentration, wetness duration and plant age on disease development by Exserohilum prolatum in itchgrass (Rottboellia cochinchinensis) - Alloub, Hala; Juraimi, A.S.; Rajan, A. Rajan; Sasttroutomo, S. Sasttroutomo (Gezira Journal of Agricultural Science; Vol 8 No 1 (2010), 2010)
Exserohilum prolatum , a fungus isolated from diseased itchgrass plants in Peninsular Malaysia, has been considered as a potential agent for biological control of this serious grass weed. Inoculum concentration, wetness duration and itchgrass age significantly influenced disease development by E . prolatum in itchgrass when evaluated in glasshouse experiments. Disease development increased with increasing inoculum concentration from 2x10 4 to 2x10 7 conidia/ml. As wetness duration increased, disease development increased. Complete kill of itchgrass at 3 to 4 leaf stage was obtained at 2x10 6 conidia/ml and a 24 hr dew period. However, when formulated in 0.01% Tween 20 and 2% palm oil, E . prolatum reduced wetness duration requirement, and exposure to 12 hr dew period resulted in 80% reduction in itchgrass shoot dry weight. Susceptibility of itchgrass to the fungus decreased with increasing plant age. Itchgrass at two to six leaf stages were the most susceptible to fungus infection. يعتبر فطر(Exserohilum prolatum)  والذي تم عزله من عشبة أم بليلة في شبه جزيرة ماليزيا وسيلة مكافحة إحيائية فاعلة لهذه العشبة النجيلية الضارة. عوامل تركيز اللقاح ، فترة الرطوبة وعمر النبات أثرت معنوياً على تطور المرض بواسطة (E. prolatum) في عشبة أم بليلة عندما قيّمت بتجارب داخل صوبة زجاجية. وقد تلاحظ أن تطور المرض قد إرتفع إرتفاعاً معنوياً مع إرتفاع معدل تركيز اللقاح منx 2  104 وإلى 2 x 107 كونيديا/مل. من ناحية أخرى تلاحظ أن شدة الإصابة بالمرض إزدادات معنوياً بإزدياد فترة الرطوبة. هذا وقد حدت موت كلي للعشبة عمر 2-3 ورقات عندما تمت معاملتها بواسطة تركيز لقاح 2x106 كونيديا/مل وفترة رطوبة 24 ساعة. أدى إستخدام عامل إنتشار Tween 20 بنسبة 0.01% وزيت النخيل بنسبة 2% إلى تقليص الحاجة إلى فترة رطوبة ممتدة (24 ساعة) حيث إنخفض الوزن الجاف للمجموع الخضري بنسبة 80% عند معاملة العشبة بفترة رطوبة بلغت 12 ساعة. أبانت النتائج أن قابلية العشبة للإصابة بالفطر قد إنخفضت مع تقدم عمر النبات وأن الأعشاب عمر 2-6 ورقات كانت أكثر قابلية للإصابة.